2016
DOI: 10.1111/ele.12651
|View full text |Cite
|
Sign up to set email alerts
|

Parameterisation and validation of a resource budget model for masting using spatiotemporal flowering data of individual trees

Abstract: Synchronised and fluctuating reproduction by plant populations, called masting, is widespread in diverse taxonomic groups. Here, we propose a new method to explore the proximate mechanism of masting by combining spatiotemporal flowering data, biochemical analysis of resource allocation and mathematical modelling. Flowering data of 170 trees over 13 years showed the emergence of clustering with trees in a given cluster mutually synchronised in reproduction, which was successfully explained by resource budget mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
85
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(90 citation statements)
references
References 53 publications
(147 reference statements)
5
85
0
Order By: Relevance
“…Our analysis does not provide a definitive test of either model, but our finding of stronger support for the resource‐limited floral induction model for seed production, rather than pollen production, hints at higher resource costs of fruits (Satake and Iwasa , Abe et al. ). Nevertheless, in such species selection likely favored the level of a “full” (mast) seed crop to be greater than the annual resource increment, ultimately providing pollination efficiency benefits associated with the economies of scale (Nilsson and Wastljung , Smith et al.…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…Our analysis does not provide a definitive test of either model, but our finding of stronger support for the resource‐limited floral induction model for seed production, rather than pollen production, hints at higher resource costs of fruits (Satake and Iwasa , Abe et al. ). Nevertheless, in such species selection likely favored the level of a “full” (mast) seed crop to be greater than the annual resource increment, ultimately providing pollination efficiency benefits associated with the economies of scale (Nilsson and Wastljung , Smith et al.…”
Section: Discussionmentioning
confidence: 63%
“…In contrast, in mast flowering species, weather cuing and resource dynamics likely drive an intensity of flowering (Abe et al. , Monks et al. , Pearse et al.…”
Section: Discussionmentioning
confidence: 99%
“…negative response to temperature and positive to precipitation 2 yr before masting; Table ). The negative correlation with MAX JUL‐2 could be related to resource accumulation in cooler years (‘priming’ the trees to respond to increased temperature 1 yr later, sensu Richardson et al ., ), an interpretation that is consistent with a model of masting that includes an element of carbon and/or nitrogen limitation (Sala et al ., ; Müller‐Haubold et al ., ; Monks et al ., ; Abe et al ., ; Pearse et al ., ; Fernandez‐Mart?nez et al ., ). Indeed, a higher soil moisture due to more precipitation and lower summer temperatures has been shown to increase litter mass loss and N mineralisation and uptake (Gessler et al ., ; Smaill et al ., ), which favours masting in beech (Han et al ., ; Miyazaki et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Pollen dispersion of Fagaceae from March to June at Ito during 2004 to 2017 (Table 1): year dates of initial pollen observed, of pollen release began, of final pollen observation, of maximum pollen dispersion and maximum pollen counts. Each average value and standard deviations: 7±21-Mar, 25±8-Mar, 14±11-Jul, 1±9-May and 135±95 grain/cm 2 . AWe found that the airborne pollen count of the date of maximum pollen dispersion tends to be large in the year with much total airborne pollen although there are not correlations between total airborne pollen and the date of initial pollen observed, between the date of pollen release began and the date of final pollen observation as a result of the regression analysis.…”
Section: Resultsmentioning
confidence: 99%